An attempt to develop a Biped Intelligent Machine BIM-UIA - Akhtaruzzaman, Md.; Shafie, Amir Akramin (2011)
Human like sovereign system that is capable to adapt itself with the changes of its environment and continue to reach its goal is considered as Humanoid Robot. In recent years much progress has been done in the design and development of humanoid and still there have a lot of opportunities in this field. Strategies of lower torso are concern for many researchers to make the system navigating as like as a normal human being do. Designing the toe, ankle, knee, hip and west for lower torso is the complicated and challenging task. Analyzing the walking gait, optimal control of multiple actuators, designing the Degree of Freedom (DoF), adaptability control and intelligence are also the ambitious tasks to make a humanoid to act like a human. This paper exemplifies the initiatives to design and development of a Biped Intelligent Machine (BIM) for Universiti Islam Antarabangsa (UIA) called BIM-UIA, in order to meet the demand of a research platform for humanoid robot navigation system. The paper represents the basic prototype design of the system as the outcomes of the study, mechanical design of a single leg having 6 DoF, component selection schemes, design of the control architecture and hip joint strategy based on three different models. This work is basically a small part of the main project but have a great inspiration for the researchers with the aim to design and construct the future BIM-UIA with lower cost and limited time constraints.